The captured economy : how the powerful enrich themselves, slow down growth, and increase inequality - Lindsey, Brink; Teles, Steven Michael (Tantor Media, 2018)
For years, America has been plagued by slow economic growth and increasing inequality. Yet economists have long taught that there is a tradeoff between equity and efficiency--that is, between making a bigger pie and dividing it more fairly. That is why our current predicament is so puzzling: today, we are faced with both a stagnating economy and sky-high inequality. In The Captured Economy, Brink Lindsey and Steven M. Teles identify a common factor behind these twin ills: breakdowns in democratic governance that allow wealthy special interests to capture the policymaking process for their own benefit. They document the proliferation of regressive regulations that redistribute wealth and income up the economic scale while stifling entrepreneurship and innovation. When the state entrenches privilege by subverting market competition, the tradeoff between equity and efficiency no longer holds. Over the past four decades, new regulatory barriers have worked to shield the powerful from the rigors of competition, thereby inflating their incomes--sometimes to an extravagant degree. Lindsey and Teles detail four of the most important cases: subsidies for the financial sector's excessive risk taking, overprotection of copyrights and patents, favoritism toward incumbent businesses through occupational licensing schemes, and the NIMBY-led escalation of land use controls that drive up rents for everyone else. Freeing the economy from regressive regulatory capture will be difficult. Lindsey and Teles are realistic about the chances for reform, but they offer a set of promising strategies to improve democratic deliberation and open pathways for meaningful policy change. An original and counterintuitive interpretation of the forces driving inequality and stagnation, The Captured Economy is a "must-listen" for anyone concerned about America's mounting economic problems and the social tensions they are sparking.